2021
DOI: 10.1016/j.heliyon.2021.e07277
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oral administration of Aureobasidium pullulans-cultured fluid containing β-glucan on concanavalin A injected mice

Abstract: A black yeast, Aureobasidium pullulans , extracellularly produces β-(1,3), (1,6)-D-glucan (β-glucan) under certain conditions. The β-glucan is known to be an immunomodulatory agent, and β-glucan enriched A. pullulans cultured fluid (AP-CF) is used in supplements to maintain human health. Concanavalin A (ConA) is a lectin, and when injected it is known to cause T cell mediated autoimmune hepatitis in mice. The present study investigated the effects of oral administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This phenomenon may account for a delicate regulation between the inflammation response and Salmonella obliteration of sophy β-glucan on Caco-2 cell under the SE challenge. Similarly, previous studies have demonstrated that the oral administration of soluble exopolysaccharide β-1,3/1,6-glucan from a black yeast, A. pullulans-cultured fluid could alleviate inflammatory responses by modulating immune cells' activity and attenuating the expression of these pro-inflammatory cytokines in vivo and in vitro under an inflammatory stimulus [19,44,45]. Thus, our findings suggested that sophy β-glucan might be an effective immune modulator and a potential anti-inflammatory agent for the treatment of salmonellosis.…”
Section: Discussionmentioning
confidence: 81%
“…This phenomenon may account for a delicate regulation between the inflammation response and Salmonella obliteration of sophy β-glucan on Caco-2 cell under the SE challenge. Similarly, previous studies have demonstrated that the oral administration of soluble exopolysaccharide β-1,3/1,6-glucan from a black yeast, A. pullulans-cultured fluid could alleviate inflammatory responses by modulating immune cells' activity and attenuating the expression of these pro-inflammatory cytokines in vivo and in vitro under an inflammatory stimulus [19,44,45]. Thus, our findings suggested that sophy β-glucan might be an effective immune modulator and a potential anti-inflammatory agent for the treatment of salmonellosis.…”
Section: Discussionmentioning
confidence: 81%